Literasi Digital Mahasiswa Sejarah Peradaban Islam IAIS Sambas Dalam Menulusuri Sumber Sejarah Lokal - Azwar Azwar; Zulfikar Ghazali; Rendi Purnama (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of digital technology connected to the internet network provides easy access to information. With the existence of digital technology devices, information is increasingly easy to obtain, process, and obtain, causing an information explosion. This information explosion makes it difficult to sort and select valid information. So that digital literacy is needed to be able to select and sort, process and redistribute information obtained from digital devices. Students of the History of Islamic Civilization (SPI) are required to be people who are required to be able to absorb information, especially information about history. The local history of Sambas Regency has not been widely published through print or digital media. So that literacy skills are needed to trace the sources and information of Sambas local history. This research uses qualitative research methods to see the literacy skills of SPI students. The results of this study indicate that SPI IAIS Sambas students have digital literacy skills obtained from Computer Practice lecture material. The material provides a basis for searching information using digital devices. Information obtained through digital data they process with careful review to avoid invalid information. Information that has been checked and re-processed so that it can be published to the public.